S110 Hif2a deletion in the pulmonary endothelium prevents hypoxia-induced pulmonary hypertension. (15th November 2017) - Cowburn, AS; Crosby, A; Macias-Gutierrez, D; Southwood, M; Branco, C; Morrell, N; Chilvers, ER; Johnson, RS
Abstract : Pulmonary arterial hypertension is a progressive and irreversible disease that leads eventually to right heart failure and death. The pathogenesis of this condition involves proliferation of endothelial and smooth muscle cells resulting in vascular remodelling of the pulmonary arterioles. Several factors are implicated in the remodelling process driven by hypoxia including stabilisation of hypoxia-inducible transcription factors (HIFs), HIF1α and HIF2α. Previous studies have shown that heterozygous deletions of HIF1α or HIF2α partially attenuate many of the remodelling process associated with the development of PAH. Consistent with these observations we have found that pulmonary endothelial specific deletion of HIF2α, achieved using murine cre-loxp technologies (L1 or alk1-cre), offers protection against hypoxia-induced PAH. The rise in pulmonary artery pressure (PAP) normally observed following chronic hypoxic challenge was absent in mice with pulmonary endothelial HIF2α deletion. The right ventricular systolic pressure of L1cre- HIF2α mice post hypoxic challenge (26.17±1.67 mmHg, n=7) was not significantly different from untreated WT mice (22.48±1.19 mmHg, n=9) and much lower than the hypertensive values seen in WT littermate controls (41.91±1.88 mmHg, n=12, p<0.0001) and L1cre-HIF1α mice (36.25±2.37 mmHg, n=7, p<0.005). Only minimal remodelling was observed in lung sections from L1cre-HIF2α mice reflecting the normal physiological PAPs following chronic hypoxia. We next questioned whether deletion of lung endothelial HIF2α would be sufficient to reduce downstream arginase-1 and −2 gene expression and in turn influence plasma nitrite/nitrate (NO(X) ) concentrations, which would be indicative of changes in nitric oxide homeostasis. The expression of both arginase-1 and −2 were significantly reduced in hypoxia-conditioned whole lung samples from L1cre-HIF2α mice relative to WT littermate controls. Plasma NO(X) concentrations were also significantly elevated in the HIF2α mutant mice when compared to plasma from WT control mice. These observations fit a model whereby reduced arginase-1/2 expression leads to increased availability of l-arginine, and in turn increased NO synthesis via NO synthases. These data offer new insights into the role of pulmonary endothelial HIF2α in causing PAH, and offer new therapeutic opportunities for the treatment of this condition.